Особенности проектирования высокочастотных КМОП ИC для генераторов с кварцевой стабилизацией частоты - Verbitskiy, V. G.; Virozub, T. M.; Voschinkin, A. F.; Zolotarevskiy, V. I.; Samotovka, V. L.; Samotovka, L. I. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
The use of certain circuit and constructive decisions when designing of two variants high-frequency CMOS integrated schemes for generators with quartz stabilization of frequency allowed to considerably improve a number of parameters in comparison with foreign samples. In the article the technique is given for designing and calculation of entrance intensifying cascades of generation blocks, designing of operating signals shapers of the target buffer for the purpose of maintenance of symmetry required of the powerful target cascade impulses and reduction of consumption current of this cascade, and therefore, of CMOS IC integrally.